MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR DENGAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA MATERI MENGIDENTIFIKASI KARAKTERISTIK GEOGRAFIS INDONESIA SEBAGAI NEGARA KEPULAUAN/MARITIM DAN AGRARIS - Neneng Hafsah (Universitas Pakuan, 2022)
IMPROVING LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS USING PICTURE AND PICTURE LEARNING MODELS ON MATERIALS IDENTIFYING GEOGRAPHICAL CHARACTERISTICS OF INDONESIA AS AN ARCHIPELAGIC/MARITIME AND AGRARIAN COUNTRYAbstract. This research departs from the phenomena that occur in the classroom that the students' understanding and learning outcomes are low on the sub-themes of humans and the environment about identifying the geographical characteristics of Indonesia as an archipelagic/maritime and agrarian country. Therefore, a teacher needs to consider learning strategies so that they can improve student learning outcomes. This study aims to determine the Picture and Picture learning model can improve student learning outcomes, to describe the process of improving student learning outcomes, to measure the magnitude of the increase in student learning outcomes in the subject matter of Social Sciences sub-theme of humans and the environment about identifying the geographical characteristics of Indonesia as an archipelagic country/maritime and agriculture in grade V Elementary School. The results of this study indicate that using the Picture and Picture learning model can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using the Picture and Picture learning model, student learning outcomes only reached an average value of 63.68 then there was an increase after using the Picture and Picture learning model to 72.35 in cycle 1 and 81.18 in cycle 2. It can be concluded that the use of the learning model Picture and Picture fun so that there is an increase in student learning outcomes. Therefore, it is recommended that the use of the Picture and Picture learning model be socialized and used as an alternative in learning Social Sciences in schools in the Bogor City Education environment.